2009
DOI: 10.4319/lo.2010.55.1.0324
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic niches and trophic levels of myctophid fishes and their predators in the Southern Ocean

Abstract: We report the trophic structure of a myctophid assemblage by measuring the isotopic niches of 14 species living in Kerguelen waters, southern Indian Ocean. Most of the species show distinct isotopic niches that differ by at least one of the two niche axes (d 13 C habitat and d 15 N trophic position), indicating trophic partitioning within the assemblage. Strong niche segregation occurs within each of the three most common genera of myctophids (Electrona, Gymnoscopelus, and Protomyctophum), illustrating the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
158
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(169 citation statements)
references
References 44 publications
10
158
1
Order By: Relevance
“…Copepods and mesopelagic fish, particularly myctophids, are important primary and secondary consumers of the phytoplankton in these waters and form an alternative food web for squid, predatory mesopelagic fish, and penguins (Kozlov, 1995;Cherel et al, 2010;Murphy et al, 2016). Measured rates of microzooplankton grazing (Jones et al, 1998;Griffiths et al, 1999;Safi et al, 2007;Pearce et al, 2011), together with high grazer biomass (Kopczyńska et al, 2001) suggest that grazers consume much of the primary productivity in this region.…”
Section: Sub-antarctic Zonementioning
confidence: 99%
“…Copepods and mesopelagic fish, particularly myctophids, are important primary and secondary consumers of the phytoplankton in these waters and form an alternative food web for squid, predatory mesopelagic fish, and penguins (Kozlov, 1995;Cherel et al, 2010;Murphy et al, 2016). Measured rates of microzooplankton grazing (Jones et al, 1998;Griffiths et al, 1999;Safi et al, 2007;Pearce et al, 2011), together with high grazer biomass (Kopczyńska et al, 2001) suggest that grazers consume much of the primary productivity in this region.…”
Section: Sub-antarctic Zonementioning
confidence: 99%
“…Analysis of carbon and nitrogen stable isotopes represent a longer period in the animal's lifecycle and have been recognized as an effective method to complement feeding ecology studies based on stomach contents of marine mammals (Knoff et al 2008, Gross et al 2009, Barros et al 2010, Kiszka et al 2010, Newsome et al 2010, Caut et al 2011. The basic principle of this technique is that the isotopic composition of consumers is derived from the isotopic composition of their food (e.g., Kelly 2000, Cherel et al 2010. In marine systems, several studies have shown that there are consistent differences between the isotopic composition of animals living in pelagic vs. benthic environments, and among estuarine, nearshore and offshore environments (France 1995, Kurle & Gudmundson 2007, Cherel & Hobson 2007, Newsome et al 2010, Ohizumi & Nobuyuki 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The mesopelagic (or pelagic) taxa contributing to otolith assemblages compare well with the short-lived, immensely abundant component reaching the sea bottom by pulses, while the benthic-benthopelagic taxa reflect a longer-term accumulation trend. In the recent, the mesopelagic taxa are a numerically significant component in the water column, being also largely responsible of the deep scattering layer (DSL, see e.g., Barham, 1966), situated at a lower trophic level (Cherel et al, 2010). The benthic and benthopelagic taxa (e.g., Gadiformes) are mainly long-lived species at a higher trophic rank (Drazen, 2008).…”
mentioning
confidence: 99%